Comparison of the effects of propofol-ketamine (ketofol) mixture in combination of IV fentanyl pretreatment during induction and proseal laryngeal mask airway (LMA) insertion - Bahuri, Nor Fahmi Ahmad (2015)
Background and Aims: The renewed interest in combination of propofol-ketamine as a mixture for sedation and anaesthesia had leaded us to search for a suitable mixture to be used for induction of anaesthesia. This study was conducted to compare the effects of two different mixture of propofol–ketamine on haemodynamic stability, adequate condition for Proseal LMA insertion and occurrence of apnoea after induction. Settings and Design: A randomized double-blinded, controlled trial was conducted in Hospital Universiti Sains Malaysia between June 2014 and October 2014. Patients and Methods: A total of 88 patients were recruited and randomized into two groups using block randomization. One group of patients was given propofol-ketamine with 1:1 ratio; whereas another group was given propofol-ketamine 1:0.5 ratio. Haemodynamic monitoring was measured at baseline, 1 minute, 5 minute and 10 minutes after induction. Proseal was inserted in each patient after successful induction. LMA scoring and apnoea scoring were recorded. Results: In regard to within-intervention-group-effect comparisons, both 1:0.5 and 1:1 propofol / ketamine ratio groups showed statistically significant changes in SBP, DBP, MAP and HR nearly across all time points. However, regarding between-and-within-intervention-group comparisons (i.e. comparison of SBP, DBP, MAP and HR between intervention groups across time points), there were no significant marginal mean differences noted between both propofol / ketamine ratio groups across time. The medians percentage of oxygen saturation was exactly the same for both groups of intervention. There was no significant difference in mean Proseal LMA score between the two groups. There were also no significant predictors between associated with Proseal LMA score. The 1:1 propofol / ketamine ratio group has higher percentage of prolonged apnoea than 1:0.5 propofol/ketamine group (90.9% vs 13.6; p < 0.001). There were two significant predictors for apnoea score which were BMI (adjusted OR 1.148, 95% CI 0.964, 1.583) and intervention group (adjusted OR 49.765, 95% CI 12.789, 193.649) Conclusions: Propofol/ketamine mixture with 1:0.5 ratio was better than propofol/ketamine 1:1 because it caused lesser association to apnoea occurrence. However the haemodynamic response were stable and comparable in both groups.